Isolation and Identification of Bacteria in the Integrated Laboratory of the Faculty of Medicine, Moslem Indonesia of University - Karim, Marzelina; Hattah, Dhian Karina Aprilani; Haris, Haslianti H.; Churiani, Churiani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
The integrated laboratory is one of the learning facilities at the university, especially to support the implementation of practicum. In laboratories that are full of activities, bacterial contamination often occurs which can interfere with the smooth running of research and practicum. This contamination is often caused by a lack of sterility in the work process and less than optimal indoor air quality. Therefore, it is important to know the type and number of bacteria found in the laboratory to prevent further spread of contamination. This study aims to isolate and identify bacteria in the Integrated Laboratory of the Faculty of Medicine, Universitas Muslim Indonesia. The method used in this study was descriptive research with a laboratory observational design, which was carried out by macroscopic and microscopic means to determine the type of microorganisms and the number of bacterial colonies. The results showed four types of bacteria found, namely Staphylococcus sp., Klebsiella pneumoniae, Staphylococcus epidermidis, and Bacillus sp., which were isolated from air and swab results. Airborne bacteria had the highest number of colonies at 14 CFU, while swab bacteria were found at 200 CFU. Although bacterial colonies were found in the laboratory, this number is still considered safe for the number of bacteria in the laboratory. Based on these findings, it is recommended that laboratory facilities pay more attention to aspects of cleanliness and sanitation as a whole.